New stirrup detailing schemes for shear demands in pile cap beams - Murty, D. S. R.; Rao, G. Papa (Journal of Structural Engineering, 2024)
Successful performance of reinforced and pre-stressed concrete members requires an effective interaction between concrete and reinforcing steel. Not only is an adequate amount of reinforcement needed but it must also be properly detailed to insure satisfactory member behaviour under all loading conditions. Pile cap is an intermediary structural element to transfer super structure vertical load, through a column to deep foundation, a group of piles. Pile caps resemble beams or slabs, depending on their plan geometry, and are subjected mainly to flexure or direct tension, one way shear, and two-way shear. Pile cap beam depth has to cater to several requirements. Primarily pile cap depth is kept large enough to permit uniform and equal load transfer to all piles below the cap, it has also to be deep enough to disallow punching of stanchion and piles through pile cap, to provide needed development length for stanchion bars and pile bars, to resist bending moment and to resist one way shear force with or with out shear reinforcement. Generally pile cap depth required for one way shear to keep shear stress below permissible levels (in the case of no shear reinforcement) is more than that required for flexure. Many hand books and designers currently omit shear design, in pile caps, lowering the shear stress to permissible limits by increasing pile cap depth. But the use of reinforcement to resist shear force is increasingly implemented in recent years, with lesser pile cap depths; this change responds to the need for simplified form work and easy construction practice, in abnormal and adverse construction conditions such as river beds, high water table, sea and coastal areas. Provision of shear reinforcement eases construction activity in diffi cult sites. However for shear demands, the conventional closed stirrups present problems in the placement of stirrup reinforcement in complex steel cages, concrete compression and construction time of pile caps. In place of inconvenient, highly involved and expensive closed stirrups, an alternative, easy and more convenient stirrup detailing, comprising two-piece “C” shaped open stirrups (twopiece stirrups) joined together in the top and bottom faces of beam, with adequate anchorage, are proposed in this experimentalstudy. Similar to pile cap beams, large beams are encountered in several other structures. The same facility of two-piece stirrup detailing proposed now, can be extended to beams wherever they occur. Two series of beams, having sixspecimens, were designed and tested, to compare the strength and performance of beams with single piece closed stirrups and two-piece stirrups. The tests undertaken satisfi ed the prime aim of the investigation, demonstrating that two-piece stirruped specimens exhibited marginally higher ultimate strength and equal serviceability criteria, in terms of smaller crack widths and deflections at service load, compared to the companion single piece closed stirruped specimens